Putri Bangsawan, Takdir, dan Pilihan: Kajian Sastra Bandingan Tokoh Merida dalam Film Brave dan Putri Mandalika dalam Buku Cerita Rakyat Putri Mandalika Sebuah Legenda dari Tanah Bumi Gora - Made Arya Vidiarama (Tadris Bahasa Indonesia, Fakultas Tarbiyah, Institut Agama Islam Negeri Madura, 2025)
This study aims to compare the story of Princess Merida in the film Brave and Princess Mandalika from the book Cerita Rakyat Putri Mandalika Sebuah Legenda dari Tanah Bumi Gora. Both characters are noble princesses who experience similar fates and conflicts but choose different paths to resolve their dilemmas. This research employs a qualitative descriptive method with a comparative literature approach. The findings reveal several similarities and differences in the narratives of Princess Merida and Princess Mandalika. These similarities and differences can be seen in the characterization, plot, as well as the settings of time and place. Moreover, the values conveyed in both stories also reflect comparable and contrasting elements.